Calcified hydatid cyst of the orbit - Rachid Aloua; Faiçal Slimani (Elsevier, 2021)
The authors report a case of calcified cystic hydatid disease of orbit and its classical management.A 13-year-old female patient presented with unilateral progressive non-pulsatile proptosis of the right eye. Ocular examination revealed proptosis of the right eye, associated with reduced (poor) vision. In morocco as an endemic country, the orbital hydatid cyst should be considered as a differential in a child patient presenting with unilateral proptosis living in animal breeding areas.